Ancient Greece - McRae, Anne. (Florence, Italy : McRae Books, 2008)
An introduction to the ancient Greeks, providing information about Greek religion, art and architecture, war, food, clothing and jewelry, and other aspects of their lives.
Includes index.
6.6
3-6
Keywords: Greece -- Civilization -- To 146 B.C. -- Juvenile literature; Greece -- Civilization -- To 146 B.C.; Greece -- Civilization